2015
DOI: 10.1016/j.cortex.2014.08.025
|View full text |Cite
|
Sign up to set email alerts
|

Sound symbolism scaffolds language development in preverbal infants

Abstract: A fundamental question in language development is how infants start to assign meaning to words. Here, using three Electroencephalogram (EEG)-based measures of brain activity, we establish that preverbal 11-month-old infants are sensitive to the non-arbitrary correspondences between language sounds and concepts, that is, to sound symbolism. In each trial, infant participants were presented with a visual stimulus (e.g., a round shape) followed by a novel spoken word that either sound-symbolically matched ("moma"… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

11
178
3
5

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 150 publications
(197 citation statements)
references
References 38 publications
11
178
3
5
Order By: Relevance
“…The stronger inter-regional communication in the left hemisphere in Asano et al's infants [68] thus may indicate that the sound-shape pairings were processed in the language-processing network (in the left hemisphere) in 11-month-old infants.…”
Section: Neural Response To Sound Symbolism In 11-month-old Infantsmentioning
confidence: 99%
See 2 more Smart Citations
“…The stronger inter-regional communication in the left hemisphere in Asano et al's infants [68] thus may indicate that the sound-shape pairings were processed in the language-processing network (in the left hemisphere) in 11-month-old infants.…”
Section: Neural Response To Sound Symbolism In 11-month-old Infantsmentioning
confidence: 99%
“…Previous research has shown that at 11 months, the language-processing network in the infant's brain responded to sound symbolism [68], but it is not clear whether they were able to establish the word -referent associations and retain it in memory. We demonstrated that sound symbolism facilitates word learning in 14-month-old Japanese-speaking infants [69].…”
Section: Sound Symbolism Scaffolds Acquisition Of Word Meaning (A) Esmentioning
confidence: 99%
See 1 more Smart Citation
“…By the time referential communication fully develops, towards the end of the first year of life, (e.g., Bates, Camaioni, & Volterra, 1975; also see, Marno et al, 2015); infants' neural activity reflects sensitivity to non-arbitrary relationships between linguistic labels and shapes. Asano et al, (2015) recorded neurophysiological responses from eleven-month-old Japanese infants and found evidence for a more effortful integration process when hearing a sound symbolic mismatch ("kipi"), as opposed to a sound symbolic match ("moma"), after the visual presentation of a round shape.…”
Section: Introductionmentioning
confidence: 99%
“…An example of this could be when a word denoting something small contains phonemes that are sound symbolically associated with smallness (i.e., an instance of indirect iconicity, discussed later). These congruencies can have effects on language learning (e.g., Asano et al, 2015;Imai, Kita, Nagumo, & Okada, 2008;Perry, Perlman, & Lupyan, 2015; for a review, see Imai & Kita, 2014) and processing (e.g., Kanero, Imai, Okuda, Okada, & Matsuda, 2014;Lockwood & Tuomainen, 2015;Sučević, Savić, Popović, Styles, & Ković, 2015). Moreover, sound symbolic associations have also been shown to impact cognition more broadly, including effects on action (Parise & Pavani, 2011;Rabaglia, Maglio, Krehm, Seok, & Trope, 2016;Vainio, Schulman, Tiippana, & Vainio, 2013;Vainio, Tiainen, Tiippana, Rantala, & Vainio, 2016), memory (Lockwood, Hargoort, & Dingemanse, 2016;Nygaard, Cook, & Namy, 2009;Preziosi & Coane, 2017), and categorization (Ković, Plunkett, & Westermann, 2010;Lupyan & Casasanto, 2015; for a recent review of sound symbolism effects, see Lockwood & Dingemanse, 2015).…”
mentioning
confidence: 99%